Relationship Response Time Handling Stroke Patients With Anxiety of Patients Family in Emergency Room - Lasaka, Hendratmo; Fawzi, Alfian; Rusmawati, Aprin; Ellina, Agusta Dian (Universitas STRADA Indonesia, 2019)
Background: Response time that is done to stroke patients when taken to hospital causes anxiety problem for the patient's family, this is due to family concerns about the health condition of family members who are waiting for the queue of action.Purpose: The purpose of this study is to know the relationship response time of stroke patients with anxiety in the patient's family in the Emergency Room.Method: This research design was a correlational analytic with cross sectional approach. The population were all families of stroke patients in the Emergency Room of Luwuk Regional Hospital averagely 35 patients per month, with accidental sampling technique obtained sampleas many as 33 respondents. The independent variable was Response time with the dependent variable Anxiety. Data collection using a questionnaire. Data analysis using Spearman Rank test on ? = 0.05.Result:The results showed that most respondents received response time in the right category, as many as 21 respondents (63.6%) and most respondents had an anxiety level in the moderate category, as many as 17 respondents (51.5%).analysis results Spearman Rank obtained p-value (0,000) <? (0.05) then H0 is rejected and H1 is accepted, which means there is a relationship between response time handling of stroke patients with anxiety in the patient's family in the Emergency RoomConclution: The role of nurses is crucial in raising anxiety level in both patients and their families while in the emergency room. Fast and appropriate services and no less important communication with the family is an important factor in providing certainty and educating in handling patients while in the emergency room so that families are not too worried about the situation that is happening.